Spectral-Kinetic Heterogeneity in Reactions of Nitrosyl Hemoglobin - Salhany, J. M. (1974)
When NO replaces CO in hemoglobin A in the presence of inositol hexaphosphate, the time course is heterogeneous in contrast to stripped hemoglobin A, where it is homogeneous. If nitrosyl hemoglobin is mixed with inositol hexaphosphate in the stopped-flow apparatus, an extra spectral change is observed which is the cause of the spectral-kinetic heterogeneity in the CO replacement reaction. At wavelengths isosbestic for this extra spectral change, the time courses show an accelerating rate of CO dissociation. On the other hand, the same reaction for NES-des-Arg hemoglobin (hemoglobin reacted with N-ethylmaleimide and carboxypeptidase B) in the presence of inositol hexaphosphate is homogeneous and slow, and shows isosbesty. High-resolution nuclear magnetic resonance spectra indicate that adult nitrosyl hemoglobin in the presence of inositol hexaphosphate is in the low ligand affinity state, thus offering a structural basis for the acceleration observed in the rate of CO dissociation. Hemoglobin Kansas, in the presence of inositol hexaphosphate, which starts and finishes the reaction in the low affinity state, shows a rate of CO dissociation about nine times faster than stripped hemoglobin A. We conclude from these results that (i) the CO to NO replacement reaction can include a functionally important change in the overall conformation of fully liganded hemoglobin, depending on solution conditions and protein type; (ii) the extra spectral change observed for nitrosyl hemoglobin is not the functionally dominating conformational change, but is a secondary effect within the low ligand affinity protein structure; and (iii) the functional properties of heme ligands are largely controlled by two conformational states of the protein, as seen by nuclear magnetic resonance spectroscopy.